Klinik Hewan Keliling Rumah Sakit Hewan Pendidikan Prof. Noerjanto Universitas Syiah Kuala [Mobile Veterinary Clinic of Prof. Noerjanto Hospital Teaching Veterinary Hospital of Universitas Syiah Kuala] - Sayuti, Arman; Panjaitan, Budianto; Syafruddin, Syafruddin; Adam, Mulyadi; Thasmi, Cut Nila; Roslizawaty, Roslizawaty; Rosmaidar, Rosmaidar; Siregar, Tongku Nizwan; Armansyah, Teuku; Sutriana, Amalia; Aliza, Dwinna (Buletin Pengabdian, 2024)
The long-term purpose of this community service is to support the autonomy of the university through independent income generation and to encourage the development of a culture of utilizing university research results for the community through the mobile veterinary clinic business carried out by Prof. Noerjanto Teaching Veterinary Hospital. To achieve above objectives, it was necessary to modify the existing clinic vehicle to include an operating room, mini-laboratory and pharmacy. The implementation of activities was carried out for five working days a week, by actively visiting smallholder livestock centers per village per day in the Aceh Besar areas. Services provided included livestock health consultation, treatment, vaccination (an effective measure as a form of protection for animals, synchronization of heat and artificial insemination, and assistance during birth. The diagnosis methods utilize the latest techniques, namely diagnosis and therapy techniques used in the field of veterinary medicine, which were the results of previous research. Mobile Clinic of Prof. Noerjanto's Teaching Veterinary Hospital had been modified by providing an operating table, mini laboratory, pharmacy, and repainting the car, thus increased the attractiveness of the community during the activities were carried out. Mass treatment of livestock in Aceh Besar district had reached the target which services covered five sub-districts. In conclusion, the mobile veterinary clinic in 2017 has successfully modified the clinic car and provided health services in 5 sub-districts in Aceh Besar District.